A tale of two cities : global change, local feeling, and everyday life in the North of England : a study in Manchester and Sheffield - Taylor, Ian, 1944-2001; Evans, Karen, 1961-; Fraser, Penny, 1966- (International library of sociology., 1996)
A Tale of Two Cities is a study of two major cities, Manchester and Sheffield. Drawing on the work of major theorists, the authors explore the everyday life, making contributions to our understanding of the defining activities of life.